PELATIHAN TEKNIS APLIKASI PENGONTROL KEUANGAN KELUARGA UNTUK IBU-IBU PKK GUNA MEMBANTU PENGAWASAN FINANSIAL MENUJU KELUARGA SEJAHTERA - Fiby Nur Afiana; Retno Waluyo; Jeffri Prayitno Bangkit Saputra; Farah Setyaningsih; El Syafangatun Aulia Difa (Nusantara Hasana Journal, 2023)
A mother has a very strategic role in the family. Where most of the family shopping activities are controlled by the mother. Proper financial management can guarantee future financial plans, have protection from unexpected expenses and make financial life more organized. When talking about money, of course it must be open and transparent. With the discipline of making a household budget, communication between partners will run more smoothly. Members of the PKK in Purwosari Village have limitations in financial management. They tend to manage finances as is without any tools so that unexpected problems often occur in the family. Besides that, lack of time and lack of information are the main obstacles faced by mothers, the cell phones they have only focus on being a communication tool without using other fields. In this modern era, there are actually many financial regulatory applications that mothers can use, such as the My Family Finance Application, My Mother’s Savings and My Financial-Personal Finance Assistant. The benefit of using this financial application is that it can record all incoming and outgoing cash flows within a certain period of time. So that it can make the family of PKK mothers become a family that is prosperous, independent and sakinah